Linguistic Intuitions. Issue 8 (5th August 2013) - Maynes, Jeffrey; Gross, Steven
Abstract: Linguists often advert to what are sometimes called linguistic intuitions . These intuitions and the uses to which they are put give rise to a variety of philosophically interesting questions: What are linguistic intuitions – for example, what kind of attitude or mental state is involved? Why do they have evidential force and how might this force be underwritten by their causal etiology? What light might their causal etiology shed on questions of cognitive architecture – for example, as a case study of how consciously inaccessible subpersonal processes give rise to conscious states, or as a candidate example of cognitive penetrability? What methodological issues arise concerning how linguistic intuitions are gathered and interpreted – for example, might some subjects' intuitions be more reliable than others? And what bearing might all this have on philosophers' own appeals to intuitions? This paper surveys and critically discusses leading answers to these questions. In particular, we defend a 'mentalist' conception of linguistics and the role of linguistic intuitions therein.